Speed Control for High-speed Railway on Multi-mode Intelligent Control and Feature Recognition - Hou Tao; Niu Hong-xia; Fan Duo-wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper is to put forward a new speed control method for the rapid development high-speed railway system. In this method, extracting the real-time feature information according to the characteristics of high-speed railway running process, and the inference engine find the matched characteristics mode in the characteristic pattern based on the current characteristics information. Using the speed closed-loop control design method, calculated the current speed error, and then based on the current error using the multi-modal intelligent control algorithm to control, and produce a corresponding controlled variable through the control rule set. And make a simulation system to value it. The results show that it has better dynamic performance and reliable steady-state performance.It a valuable  method to provide a advanced way for the train safer, faster and more comfort. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1642